2024
DOI: 10.3390/ijms25042182
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Hormone-Binding Globulin Gene Polymorphisms and Breast Cancer Risk in Caucasian Women of Russia

Irina Ponomarenko,
Konstantin Pasenov,
Maria Churnosova
et al.

Abstract: In our work, the associations of GWAS (genome-wide associative studies) impact for sex-hormone-binding globulin (SHBG)-level SNPs with the risk of breast cancer (BC) in the cohort of Caucasian women of Russia were assessed. The work was performed on a sample of 1498 women (358 BC patients and 1140 control (non BC) subjects). SHBG correlated in previously GWAS nine polymorphisms such as rs780093 GCKR, rs17496332 PRMT6, rs3779195 BAIAP2L1, rs10454142 PPP1R21, rs7910927 JMJD1C, rs4149056 SLCO1B1, rs440837 ZBTB10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…For the genetic study, DNA was isolated from the venous blood (4-5 mL of peripheral blood) of BC, and the control using the phenol-chloroform-alcohol technique was utilized [40,41]. Before carrying out the genotyping procedure on the CFX96 device (Real-Time PCR System (Bio-Rad Laboratories, Inc., Hercules, CA, USA)) [42], all DNA samples were tested on a spectrophotometer Nanodrop-2000 (Thermo Fisher Scientific Inc., Waltham, MA, USA), with which their purity and concentration were evaluated [43,44].…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…For the genetic study, DNA was isolated from the venous blood (4-5 mL of peripheral blood) of BC, and the control using the phenol-chloroform-alcohol technique was utilized [40,41]. Before carrying out the genotyping procedure on the CFX96 device (Real-Time PCR System (Bio-Rad Laboratories, Inc., Hercules, CA, USA)) [42], all DNA samples were tested on a spectrophotometer Nanodrop-2000 (Thermo Fisher Scientific Inc., Waltham, MA, USA), with which their purity and concentration were evaluated [43,44].…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…Twin/family studies have shown that the contribution of heredity to the formation of common human diseases varies widely and can reach 50-80% (for example, for uterine fibroids-55-69% [8,9], polycystic ovaries-79% [10], blood pressure-30-68% [11][12][13][14], endometriosis-47-51% [15,16], etc.). At the same time, the currently known scientific data on candidate genes associated with the risk of developing these diseases (obtained in genome-wide association studies (GWASs) and others) only partially "describe" the genetic determinants of these diseases [17][18][19]. For example, for breast cancer, GWAS loci "describe" only about 44% of the putative genetic determinants of breast cancer (18% of 41%) [20], for endometriosis, the figure is 10% (5.19% of 51%) [21], and for blood pressure the percentage is 31-65% (19.4-21.3% of 30-68% [22], etc.).…”
Section: Introductionmentioning
confidence: 99%